Kako smo opremljali na IJS Odsek za tanke plasti in površine z raziskovalno opremo - Navinšek, Boris (Vakuumist, 1998)
In a short review I describe our ideas, actions and efforts, which were in thelast 40 years connected with the design, elaboration and application of the research equipments at our Department of thin films and surfaces. The successive development and purchase of the apparatus and measuring techniques show also how our programme was developed from the initial characterization ofreactor materials to today's plasma surface engineering.
Keywords: tanke plasti; raziskovanje; Inštitut Jožef Stefan; zgodovinski pregledi